Rhythmic adenosine triphosphate release from the cyanobacterial circadian clock protein KaiC revealed by real‐time monitoring of bioluminescence using firefly luciferase. (17th January 2021) - Mutoh, Risa; Iwata, Keita; Iida, Takahiro; Ishiura, Masahiro; Onai, Kiyoshi
Abstract: The cyanobacterial circadian clock is composed of three clock proteins, KaiA, KaiB and KaiC. This KaiABC clock system can be reconstituted in vitro in the presence of adenosine triphosphate (ATP) and Mg 2+, and shows circadian rhythms in the phosphorylation level and ATPase activity of KaiC. Previously, we found that ATP regulates a complex formation between KaiB and KaiC, and KaiC releases ATP from KaiC itself ( PLoS One, 8, 2013, e80200). In this study, we examined whether the ATP release from KaiC shows any rhythms in vitro. We monitored the release of ATP from wild‐type and ATPase motif mutants of KaiC as a bioluminescence in real time using a firefly luciferase assay in vitro and obtained the following results: (a) ATP release from KaiC oscillated even without KaiA and KaiB although period of the oscillation was not 24 hr; (b) ATP was mainly released from the N‐terminal domain of KaiC; and (c) the ATP release was enhanced and suppressed by KaiB and KaiA, respectively. These results suggest that KaiC can generate basal oscillation as a core clock without KaiA and KaiB, whereas these two proteins contribute to adjusting and stabilizing the oscillation. Abstract : We established ATP release monitoring system in vitro. ATP release from KaiC oscillated even without KaiA and KaiB although period of the oscillation was not 24 hr. This suggests that KaiC can generate basal oscillation as a core clock without KaiA and KaiB whereas these two proteins contribute to adjusting and stabilizing the oscillation.